(untitled) (Metallurgy and Foundry Engineering, 2006)
Utilization of thermo-mechanical treatment in forging medium-carbon alloyed steel including microaddition of titanium is presented. Results of forging tests carried out in industrial conditions with a use of a high-speed forging press in conventional cooling conditions are compared with those involving controlled forging and direct cooling after forging. Significant grain refinement accompanied by increase in tensile properties was observed. It was also concluded that deformation degree has an effect on the final mechanical properties.